2022
DOI: 10.21273/horttech05018-22
|View full text |Cite
|
Sign up to set email alerts
|

Single-screen Bark Particle Separation Can be Used to Engineer Stratified Substrate Systems

Abstract: Substrate stratification is an emerging substrate management strategy involving layering multiple substrate materials within a single container to modify physiochemical characteristics of the substrate system. Specifically, stratifying allows growers and researchers to rearrange the air–water balance within a container to modify hydraulic characteristics. Moreover, fertilizer can be incorporated into just the upper strata to reduce leaching. Research to date has shown benefits associated with resource efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Thus, the greater root biomass in the lower stratum may be attributed to larger roots. These results contrast the results observed by Fields et al (2022), where there were greater root biomass values measured in the upper strata than lower. However, the system used fine bark particles layered over coarse bark; thus, there were different pore diameters and distributions (peat-based substrate vs. screened fine bark particles; unscreened bark vs. screened coarse bark).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, the greater root biomass in the lower stratum may be attributed to larger roots. These results contrast the results observed by Fields et al (2022), where there were greater root biomass values measured in the upper strata than lower. However, the system used fine bark particles layered over coarse bark; thus, there were different pore diameters and distributions (peat-based substrate vs. screened fine bark particles; unscreened bark vs. screened coarse bark).…”
Section: Resultscontrasting
confidence: 99%
“…Promising results have demonstrated that substrate stratification may support possibilities for nursery growers to reduce water and fertilizer inputs by 25% and 20%, respectively, and continue producing equivalent or better crops than traditionally used nursery production methods (Criscione et al 2022a;Fields et al 2021b). Evidence has also shown improved containerized crop rooting in stratified systems when compared with conventional growing practices (Fields et al 2022). Moreover, others have used stratified substrate concepts to stratify controlled-release-fertilizer placement (Ammons et al 2022) and to reduce weed germination and associated herbicide application costs in container systems (Khamare et al 2022).…”
mentioning
confidence: 99%
“…This suggests that some aspect of solute transport in the stratified container made it more conducive for mineral nutrients to migrate from the top of the container to the bottom. However, literature has shown that pourthrough extracts result in lower EC if fertilizer is placed in the top half of the container in ), dissolved inorganic nitrogen (DIN; NH traditional (Ammons et al 2022) or in a stratified substrate (Fields et al 2022). This could be because of the distance the applied water travels and displaces (if piston flow occurs) or mixes the resident solution in the substrate as illustrated herein, or because of decreased infiltration rate, preferential flow, and water velocity when stratifying substrate (Criscione et al 2022b).…”
Section: Locationmentioning
confidence: 99%
“…As measured by quality ratings and overall growth (i.e., physiological measurements), the equal or greater performance of crops produced in the stratified substrate systems have been reported [6,[9][10][11]. In the stratified systems, improved crop growth and quality were the most notable within the first year, especially during crop establishment [6].…”
Section: Introductionmentioning
confidence: 98%